Polarização política e voto facultativo: determinantes da participação eleitoral no Brasil (2014-2022) - Pradella, Murilo (2025)
Voter turnout is a central topic in Political Science and crucial for understanding the functioning of representative democracies. This dissertation investigates the relationship between political polarization and electoral participation in Brazil, analyzing elections from 2002 to 2022. The study hypothesizes that polarized contexts amplify the effects of ideology and partisanship on voting decisions, particularly in a hypothetical voluntary voting scenario. To test this relationship, we use data from the Brazilian Electoral Study (ESEB) and official statistics from the Superior Electoral Court (TSE), examining turnout trends and voter motivations. The research mobilizes different theoretical approaches to electoral behavior, such as Rational Choice Theory, the Michigan School, and the Sociological Model, while also engaging in the debate on affective polarization. The results indicate that political polarization selectively influences electoral participation, reinforcing the mobilization of ideologically engaged voters while discouraging moderates. In a voluntary voting context, this dynamic is expected to intensify, increasing participation inequalities. This study contributes to the debate on the impact of polarization in contemporary democracies and the challenges of political participation in polarized contexts.